KONTRIBUSI MODEL PEMBELAJARAN M-APOS TERHADAP KEMAMPUAN PEMAHAMAN KONSEP MATEMATIS SISWA - Cahya Dwi Budiarti; Sigid Edy Purwanto; Benny Hendriana (FKIP Universitas Muhammadiyah Prof. DR. HAMKA, 2019)
The aim of this research is to find contribution of M-APOS model to the students’ mathematical understanding ability. This study is quantitative research and use quasi experimental with the post-test only design with nonequivalent groups. The sample of this research is 73 students gathered by using cluster random sampling. Instrument used in this research is essay test which valid and reliable. The data are from populations that are normally distributed but not homogeneous. Hypothesis test was using t’-test at significant level of 5%, obtained t’ of 1,981. This study concluded that there is the effect of M-APOS models to the students’ mathematical understanding ability, with a contribution of 0,411 which is classified as being moderate.